Wheelchair accessibility of urban rail systems: Some preliminary findings of a global overview. (October 2021) - Ferreira, Amanda Fernandes; Leite, Aline Damaceno; Pereira, Lorena de Freitas; Neves, Juliana Muniz de Jesus; Oliveira Pinheiro, Mirian Greiner de; Chang, S.K. Jason
Abstract: Personal mobility is one of the fundamental human rights and it is vital to ensuring a productive and dignified life. It is estimated that there are more than 130 million people worldwide with a physical disability that requires the use of a wheelchair. In this context, public transport plays an important role, as a key element in guaranteeing equity in mobility and access to basic needs such as education, healthcare, employment and leisure. Urban rail systems represent an important medium and high-capacity mode of transport, largely used in daily journeys, especially within larger cities. Given the background, the aim of this article is to investigate wheelchair accessibility in urban rail systems around the world. In order to present this global overview, the official websites of the 212 urban rail systems in operation in 59 countries worldwide were consulted. The systems were classified into 7 different levels of accessibility, according to their percentage of declared adapted stations. The systems were then grouped per country and per United Nations geographical region, to enable an evaluation that takes into consideration different hierarchical perspectives. The results show that Eastern Asia, Western Europe and Northern America are the locations that have the highest number of systems. However, when it comes to accessibility, Northern America still has a very heterogeneous scenario, with a significant number of "Average" systems, while Asia and Europe together have more than half of the systems classified as "Very good" or "Fully accessible". The presence of urban rail systems and the accessibility of those systems do not follow a strict pattern and some historical events are pointed to in order to try to explain the scenario. The study shows that there is still a long way to go when it comes to the accessibility of wheelchair users around the world and the lack of accessibility is not a problem only in developing countries. Highlights: The lack of accessibility is not only an issue in developing countries. The systems' accessibility level varies even among cities of the same country. 62% of all systems with good accessibility are located in Asia and Europe. 19% of the systems do not provide any information about their accessibility status. International declarations and classification documents were crucial to set the awareness about accessibility.